Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.